An unusual distribution of monomethylalkanes in Botryococcus Braunii-rich samples: Origin and significance. - Audino, Michiele; Grice, Kliti; Alexander, Robert; Boreham, Christopher; Kagi, Robert (Pergamon-Elsevier Science Ltd, 2001)
A unique distribution of four homologous series of monomethylalkanes (MMAs) ranging fromC23 to C31+ in the extractable organic matter and the hydrous pyrolysate of Permian torbanites has been observed for the first time. These components have been identified by gas chromatography-mass spectrometry and cochromatography of authentic standards. Each of the series begins with the 2-methylalkane. Each member of a particular homologous series has a common alkyl group, each series differing to the next by two carbon atoms. The members within each homologous series differ by the number of carbon atoms in the second alkyl group. These pronounced homologous series of MMAs are superimposed over the series of lower abundance, partially resolved, more commonly occurring MMAs. This distinct contrast in the distributions of the novel MMAs series and the more commonly occurring MMAs suggests two distinct sources of MMAs in the torbanites. This visual observation is borne out by compound specific carbon isotopic data.A detailed molecular carbon isotopic study in combination with structural data suggests that the unusual MMA series are either derived directly from Botryococcus braunii race A or are novel biomarkers indicative of intense heterotrophic reworking of the algal biomass.